Cold Pressor Test in Primary Hypertension: A Cross-Sectional Study - Han, Yue; Du, Jun; Wang, Jing; Liu, Bin; Yan, Yu-Ling; Deng, Song-Bai; Zou, Ya; Jing, Xiao-Dong; Du, Jian-Lin; Liu, Ya-Jie; She, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Objectives To investigate the characteristics of patients with primary hypertension who had positive responses to the cold pressor test (CPT). Methods This cross-sectional study was conducted between November 2018 to November 2019, and the CPT was performed in patients with primary hypertension in 48 hospitals. The demographic characteristics and complications were collected through a questionnaire and physical examinations. A 12-month follow-up was conducted to identify the occurrence of the following events: a) all-cause mortality; b) myocardial infarction; c) stroke; d) hospitalized for heart failure. Results The CPT was positive in 30.7% of the patients. Compared with the negative CPT group, the positive CPT group was associated with a lower rate of blood pressure control, and was more likely to have a high salt diet, diabetes, hyperuricemia, left ventricular wall thickening, carotid plaques, coronary heart disease and heart failure. A high-salt diet (OR = 1.228, 95%CI: 1.037–1.456) was found to be correlated with the positive result of CPT. Among patients in the positive CPT group, those using diuretics had a significantly higher rate of blood pressure control than those not using diuretics (54.6 vs.42.6%, x2 = 6.756, P = 0.009). After a 12-month follow-up, the incidence of heart failure in the positive CPT group was significantly higher than that in the negative CPT group (7.35 vs.5.01%, x2 = 3.945, P = 0.047). Conclusions Patients with positive responses to the CPT had lower rates of BP control and a high risk of heart failure, which may be related to their preference for a high-salt diet. The use of diuretics helps to better control blood pressure in those patients.